Solar Panel Installation Engineering for Energy Conversion Optimization in Solar Power Plants - Yandri, Valdi Rizki; Mayura, Yona; Wiharti, Wiwik; Hendri, Zulka; Hendri, Lenny Novi; Mufid, Ulfiah (JECCOM: International Journal of Electronics Engineering and Applied Science, 2024)
The sunlight absorption is the main technical factor of solar power plants performance because it affects to the amount of solar energy conversion. In order to optimize this absorption, the position of solar panel should be adapted to the direction of sunlight so it can improve the economic factor of solar power plants utilization. Furthermore, in this research, we have designed and tested three serial connection solar panels with single solar tracker (SST) to optimize the absorption of sunlight and its conversion to electricity, where the electrical current from panel with SST (1.41 – 2.52 A) is higher than panel without SST (0.89 – 1.59 A). Another parameter, namely electrical power of solar power plants, is proportional to electrical current and also higher than without SST (65.2 – 102.4 W), so the stored electrical energy in battery can be also increased. The utilization of Arduino Mega 2560, driver motor BTS7960, and linear actuator can optimize the solar panel absorption and finally this control circuit addition can increase the solar energy conversion to electricity. Besides that, this control circuit will reset the position of solar panel at 6.30 pm to the starting position. It means the solar energy conversion can be maximized by using SST and this advantage can increase the efficiency and support the transition to renewable energy.